Acute NelfA knockdown restricts compensatory gene expression and precipitates ventricular dysfunction during cardiac hypertrophy. (May 2020) - Alikunju, Saleena; Severinova, Elena; Yang, Zhi; Ivessa, Andreas; Sayed, Danish
Abstract: Coordinated functional balance of negative and positive transcription complexes maintain and accommodate gene expression in hearts during quiescent and hypertrophic conditions, respectively. Negative elongation factor (Nelf) complex has been implicated in RNA polymerase II (pol II) pausing, a widespread regulatory transcriptional phenomenon observed across the cardiac genome. Here, we examine the role of NelfA aka, Wolf-Hirschhorn syndrome candidate 2 (Whsc2), a critical component of the negative elongation complex in hearts undergoing pressure-overload induced hypertrophy. Alignment of high-resolution genome-wide occupancy data of NelfA, Pol II, TFIIB and H3k9ac from control and hypertrophied hearts reveal that NelfA associates with active gene promoters. High NelfA occupancy is seen at promoters of essential and cardiac-enriched genes, expressed under both quiescent and hypertrophic conditions. Conversely, de novo NelfA recruitment is observed at inducible gene promoters with pressure overload, accompanied by significant increase in expression of these genes with hypertrophy. Interestingly, change in promoter NelfA levels correlates with the transcript output in hypertrophied hearts compared to Sham, suggesting NelfA might be playing a critical role in the regulation of gene transcription during cardiac hypertrophy. In vivo knockdown of NelfA (siNelfA) in hearts subjected to pressure-overload results in early ventricular dilatation and dysfunction, associated with decrease in expression of inducible and cardiac-enriched genes in siNelfA hypertrophied compared to control hypertrophied hearts. In accordance, in vitro knockdown of NelfA in cardiomyocytes showed no change in promoter pol II, however significant decrease in in-gene and downstream pol II occupancy was observed. These data suggest an inhibited pol II progression in transcribing and inducible genes, which reflects as a decrease in transcript abundance of these genes. These results indicate that promoter NelfA occupancy is essential for pol II –dependent transcription. Therefore, we conclude that NelfA is required for active transcription and gene expression during cardiac hypertrophy. Graphical abstract: Unlabelled Image Highlights: Adaptation of gene expression is the most fundamental response to hypertrophic stimulation Promoter negative elongation factor A (NelfA) occupancy is widespread across the cardiac genome NelfA levels increase during cardiac hypertrophy and required for active gene transcription Acute knockdown of NelfA in hypertrophying heart precipitates early onset of cardiac dysfunction